The psychophysiological stress response in psoriasis and rheumatoid arthritis. (1st April 2014) - de Brouwer, S.J.M.; van Middendorp, H.; Stormink, C.; Kraaimaat, F.W.; Sweep, F.C.G.J.; de Jong, E.M.G.J.; Schalkwijk, J.; Eijsbouts, A.; Donders, A.R.T.; van de Kerkhof, P.C.M.; van Riel, P.L.C.M.; Evers, A.W.M.
Summary: Background: Psychosocial stress can be a risk factor for the maintenance and exacerbation of chronic inflammatory diseases, such as psoriasis and rheumatoid arthritis (RA). Objectives: To gain insight into the specificity of the psychophysiological stress response during chronic inflammation, we assessed autonomic and neuroendocrine responses to stress in different chronic inflammatory diseases. Methods: Thirty patients with psoriasis (nine women, mean age 58·5 years ± 12·4), 34 patients with RA (16 women, mean age 60·8 years ± 9·2) and 25 healthy controls (16 women, mean age 55·6 years ± 8·7) underwent a standardized psychosocial stress task (Trier Social Stress Test). Salivary levels of α‐amylase and cortisol and self‐reported tension levels were measured before and after the stress test. Results: The cortisol response to stress was heightened in patients with psoriasis compared with patients with RA and healthy controls, whereas there were no differences in the autonomic and self‐reported measures. Conclusions: The altered neuroendocrine stress response in patients with psoriasis suggests that stressful events might have different physiological consequences for specific patient groups with chronic inflammatory conditions, possibly adversely affecting disease status.